2012
DOI: 10.4049/jimmunol.1102495
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cell Priming in the Presence of IFN-α Renders CTLs with Improved Responsiveness to Homeostatic Cytokines and Recall Antigens: Important Traits for Adoptive T Cell Therapy

Abstract: Previous mouse and human studies have demonstrated that direct IFN-α/β signaling on naive CD8 T cells is critical to support their expansion and acquisition of effector functions. In this study, we show that human naive CD8 T cells primed in the presence of IFN-α possess a heightened ability to respond to homeostatic cytokines and to secondary Ag stimulation, but rather than differentiating to effector or memory CTLs, they preserve nature-like phenotypic features. These are qualities associated with greater ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Indeed, we have recently demonstrated that loss of IFNAR1 stimulates growth of transplanted melanomas (Katlinskaya et al, 2016). Overall, our data are consistent with intra-tumoral IFN production being linked with CTL generation and viability (Hiroishi et al, 2000), observations that IFN may act to improve the effect of adoptive transfer of CTL (Hervas-Stubbs et al, 2012) and with recent finding that a specific CAR design, which serendipitously increased IFN signaling in CTL, evoked an augmented therapeutic effect (Zhao et al, 2015). Nevertheless, our results do not rule out additional putative cellular targets (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, we have recently demonstrated that loss of IFNAR1 stimulates growth of transplanted melanomas (Katlinskaya et al, 2016). Overall, our data are consistent with intra-tumoral IFN production being linked with CTL generation and viability (Hiroishi et al, 2000), observations that IFN may act to improve the effect of adoptive transfer of CTL (Hervas-Stubbs et al, 2012) and with recent finding that a specific CAR design, which serendipitously increased IFN signaling in CTL, evoked an augmented therapeutic effect (Zhao et al, 2015). Nevertheless, our results do not rule out additional putative cellular targets (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, intratumoral delivery of IFN-I synergized with immunotherapy (79) and chemotherapy (47) to induce therapeutic response in tumor-bearing mice that involved, in both cases, enhanced DC cross-presentation. Notably, IFN-I can enhance anti-tumor CTL responses also via direct effects on CD8 T cells, inducing their expansion and acquisition of effector functions thus improving therapeutic efficacy (80, 81). …”
Section: Importance Of DC Cross-priming For Anticancer Immune Responsmentioning
confidence: 99%
“…CTLL-2 is a stable subclone of cytotoxic T lymphocytes originally isolated from a C57BL/6 mouse and 200 U/mL of IL-2 (Preprotech) was added in its culture medium (16). Peripheral blood mononuclear cell (PBMC) were obtained from filters of blood donation units under informed consent following approval of the Institutional Ethical Committee, carboxyfluorescein succinimidyl ester (CFSE) stained and monitored as described (17). Details on the isolation of mononuclear cells from spleen, lung, and liver, as well as antibodies, flow cytometry, and immunoshistochemistry can be found in Supplementary Methods.…”
Section: Il-2rgmentioning
confidence: 99%